Halal awareness can’t improved purchase intention imported skincare - Hilda Monoarfa; Rida Rosida; Juliana; Sintiyawati; Rizuwan Abu Karim (al-Uqud : Journal of Islamic Economics, 2023)
The purpose of this study is to find out how halal awareness and online consumer reviews (OCRs) on the decision to buy imported cosmetics, besides that, to find out how the influence of halal awareness of millennials on purchasing decisions through the Online Consumer reviews (OCRs) variable as a mediator. The design of this study uses a descriptive causality technique with a quantitative approach. The analysis technique used is the Moderated Regression Analysis (MRA) with a millennial sample of 203 respondents. The results of this study indicate that halal awareness has a negative effect on purchasing decisions for imported cosmetics and is in the medium category. Halal awareness towards purchasing decisions for imported cosmetics through Online Consumer Reviews (OCRs) as a moderating variable has a significant effect and is in the moderate category. In this study, halal awareness is also hypothesized to have a negative effect on purchasing decisions, where it is researched by millennials who use imported cosmetics.